The flavonoid degrading fungus Acremonium sp. DSM 24697 produces two diglycosidases with different specificities - Weiz, Gisela; Mazzaferro, Laura S; Kotik, Michael; Neher, Bárbara D; Halada, Petr; Křen, Vladimír; Breccia, Javier D (Applied microbiology and biotechnology, 2019)
AbstractDiglycosidases hydrolyze the heterosidic linkage of diglycoconjugates, releasing the disaccharide and the aglycone. Usually, these enzymes do not hydrolyze or present only low activities towards monoglycosylated compounds. The flavonoid degrading fungus Acremonium sp. DSM 24697 produced two diglycosidases, which were termed 6-O-α-rhamnosyl-β-glucosidase I and II (αRβG I and II) because of their function of releasing the disaccharide rutinose (6-O-α-L-rhamnosyl-β-D-glucose) from the diglycoconjugates hesperidin or rutin. In this work, the genome of Acremonium sp. DSM 24697 was sequenced and assembled with a size of ~ 27 Mb. The genes encoding αRβG I and II were expressed in Pichia pastoris KM71 and the protein products were purified with apparent molecular masses of 42 and 82 kDa, respectively. A phylogenetic analysis showed that αRβG I grouped in glycoside hydrolase family 5, subfamily 23 (GH5), together with other fungal diglycosidases whose substrate specificities had been reported to be different from αRβG I. On the other hand, αRβG II grouped in glycoside hydrolase family 3 (GH3) and thus is the first GH3 member that hydrolyzes the heterosidic linkage of rutinosylated compounds. The substrate scopes of the enzymes were different: αRβG I showed exclusive specificity toward 7-O-β-rutinosyl flavonoids, whereas αRβG II hydrolyzed both 7-O-β-rutinosyl- and 3-O-β-rutinosyl- flavonoids. None of the enzymes displayed activity toward 7-O-β-neohesperidosyl- flavonoids. The recombinant enzymes also exhibited transglycosylation activities, transferring rutinose from hesperidin or rutin onto various alcoholic acceptors. The different substrate scopes of αRβG I and II may be part of an optimized strategy of the original microorganism to utilize different carbon sources.
Keywords: flavonoidy; glykosidhydrolasy; Fungal Proteins; Glycoside Hydrolases; Substrate Specificity; Flavonoids; rekombinantní proteiny; Recombinant Proteins; Recombinant protein; Glycoside hydrolase; Phylogeny; molekulová hmotnost; fungální proteiny; Sequence Analysis, DNA; Hesperidin; Rutin; sekvenční analýza DNA; Molecular Weight; substrátová specifita; fylogeneze; Pichia; Enzyme catalysis; Acremonium